Viability of Vibrio cholerae in Water - P.R.G., Varma; T.S.G., Iyer (Fishery Technology, 2025)
The viability of V. cholerae Inaba and Ogawa in distilled water, municipal water and sea water both at room temperature (28-30°C) and at refrigerated temperatures (5- l0°C) is discussed. The survival varied from 20 h in distilled water at room temperature to 38-40 days in sterile sea water at room temperature. Extended viability was noticed in all cases at refrigerated temperature and maximum viability of 165-170 days was noticed in sterile sea water at 5-l0°C.